KETERLIBATAN ORANG TUA MELALUI PENDIDIKAN NILAI DALAM MENGATASI DEGRADASI NILAI MORAL KELUARGA - Br Ginting, Susanna; Daulat Saragi; Yacobus Ndona (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
An frightening degree of moral degeneration has been attained. The family is one of the social structures that must take responsibility for this issue. The family is the first and most significant social structure where people are taught values. The family has a duty to reduce moral deterioration, notably by raising awareness, instilling, and promoting values ​​and norms that exist in society. This study aims to explain how parental engagement in reversing moral degeneration within the family can be achieved through value education. A qualitative case study research design is used in this work. This study employed document studies, in-depth interviews, and observations as data gathering methods. Thematic analysis was used as the data analysis method in this investigation. Triangulation of sources and methods was used in this study to attain a high degree of reliability. The study's findings demonstrated the various ways in which parents can get involved in their children's education: through parent associations, open lines of communication between parents and teachers, home visits, arranging parent teachers, and accompanying kids at home. Additionally, information was gathered about the challenges encountered when trying to incorporate parents in the application of value education as a means of combating moral decay in the home and establishing moral principles in children.